Association of Variability in Body Mass Index and Metabolic Health With Cardiometabolic Disease Risk. Issue 7 (April 2019) - Sponholtz, Todd R.; van den Heuvel, Edwin R.; Xanthakis, Vanessa; Vasan, Ramachandran S.
Abstract : Background: Metabolic syndrome is associated with high risk of cardiovascular disease, although risk may differ according to the specific conditions present and variability in those conditions. Methods and Results: We defined obesity (body mass index [BMI] ≥30 kg/m 2 ) and metabolic health (<2 nonobesity National Cholesterol Education Program Adult Treatment Panel III conditions) among 3632 Framingham Heart Study offspring cohort participants (mean age, 50.8 years; 53.8% women) who were followed up from 1987 to 2014. We defined participants whose variance independent of the mean for a metabolic syndrome–associated measure was in the top quintile as being "variable" for that measure. Variable metabolic health was defined as ≥2 variable nonobesity metabolic syndrome components. We investigated the interaction between obesity and metabolic health in their associations with cardiometabolic disease and cardiovascular disease using Cox proportional hazards regression. In addition, we estimated the associations of BMI variability and variable metabolic health with study outcomes within categories of obesity and metabolic health status, respectively. We observed 567 incident obesity (41 439 person‐years), 771 incident metabolically unhealthy state (25 765 person‐years), 272 incident diabetes mellitus (56 233 person‐years), 503 incident hypertension (12 957 person‐years), 589 cardiovascular disease (60 300 person‐years), and 195 chronic kidney disease (47 370 person‐years) events on follow‐up. Obesity and being metabolically unhealthy were independently and positively associated with all outcomes. BMI variability, compared with stable BMI, was associated with 163%, 67%, 58%, and 74% higher risks of having obesity, becoming metabolically unhealthy, having diabetes mellitus, and having hypertension, respectively, among nonobese participants. Variable metabolic health, compared with stable metabolic health, was associated with a 28% higher risk of cardiovascular disease, among metabolically healthy participants. Conclusions: We did not observe evidence for a positive interaction between obesity and metabolic health status with regard to study outcomes. BMI and metabolic health variability are associated with adverse health outcomes.